2023
DOI: 10.3390/foods12081719
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and Antioxidant Effect of Food Items and Matrices during Simulated In Vitro Digestion

Abstract: The digestive tract can be considered a bioreactor. High levels of reactive oxygen species (ROS) during digestion may predispose for local and/or systemic oxidative stress and inflammation, e.g., inflammatory bowel diseases. Food items rich in antioxidants may prevent such aggravation. This investigation analyzed pro-and antioxidant patterns of food matrices/items following in vitro digestion. Gastrointestinal digestion reflecting typically consumed quantities was performed on nine food items (orange and tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Hence, the decrease in phenolic concentrations (attested by spectrophotometric assays and phenolic profiling by LC-DAD-ESI/MS) upon digestion may prompt a decrease in the radical scavenging efficiency, suggesting that most of the phenolic compounds from the CS extract were degraded after digestion and/or metabolized into phenolic metabolites, with reduced bioactivity compared to the parent compounds that originate them [6,37]. In addition, previous studies on the in vitro digestion of foods and by-products obtained similar outcomes, highlighting lower antiradical properties after digestion [38][39][40].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 82%
“…Hence, the decrease in phenolic concentrations (attested by spectrophotometric assays and phenolic profiling by LC-DAD-ESI/MS) upon digestion may prompt a decrease in the radical scavenging efficiency, suggesting that most of the phenolic compounds from the CS extract were degraded after digestion and/or metabolized into phenolic metabolites, with reduced bioactivity compared to the parent compounds that originate them [6,37]. In addition, previous studies on the in vitro digestion of foods and by-products obtained similar outcomes, highlighting lower antiradical properties after digestion [38][39][40].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 82%
“…The present study investigated oxidative stress and inflammatory markers of digested food items and their combinations at the interface of the gut and the host, i.e., in a model of the small intestinal epithelium, where most macro-and micronutrients are absorbed [24]. Previous studies have suggested that ROS and pro-oxidant food compounds could especially negatively impact the gut epithelium, as ROS levels post-digestion could be high [9,16], i.e., higher than in native food items or in other body compartments that are under tight homeostatic ROS control, though surprisingly little knowledge exists in this area. As ROS is tightly linked to inflammation, food items rich in ROS or increasing ROS during digestion could also increase systemic inflammation [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, sugar-rich beverages such as sodas have been reported to increase ROS production in the short term in animal experiments [14], downregulating the body's own antioxidant defense mechanisms, while the consumption of meat can produce lipid peroxides [15]. In a previous study of ours, we have shown that lipid-rich food matrices such as white chocolate and sausage indeed result in the production of malondialdehyde (MDA), a downstream product of peroxidation during digestion, which, however, could be quenched by simultaneous ingestion of orange juice [16].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations